Female Lecturers' Psychological Well-being and Performance are Impacted by Work-family Conflict and Self-efficacy - Yuliaty, Farida (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This study aims to examine the influence of work-family conflict (WFC) and self-efficacy on the psychological well-being and performance of female lecturers in Bandung. It also explores the mediating role of psychological well-being in these relationships to provide a comprehensive understanding of how these factors interact to affect the productivity of female lecturers.Methodology: This quantitative study used a survey and Structural Equation Modeling (SEM) via SmartPLS 4 to examine relationships between WFC, self-efficacy, psychological well-being, and performance. WFC and self-efficacy were the exogenous variables, psychological well-being was the mediator, and performance was the endogenous variable. A sample of 140 married female lecturers from West Java and Banten with at least three years of experience was selected using purposive and accidental sampling.Findings: Work-family conflict (WFC) negatively affects both psychological well-being and performance, while self-efficacy positively influences both. Psychological well-being significantly enhances performance and partially mediates the effects of WFC and self-efficacy on performance, with mediation effects of 32.27% and 26.67%, respectively.Conclusion: This research highlights the importance of addressing work-family conflict and fostering self-efficacy to enhance psychological well-being and performance among female lecturers. Institutions can improve lecturer performance by supporting mental health initiatives and helping lecturers manage WFC. Additionally, increasing self-efficacy through confidence-building programs can contribute significantly to both psychological well-being and productivity. This study fills gaps in previous research by offering a nuanced understanding of the mediating role of psychological well-being in the academic context, particularly for female lecturers balancing work and family responsibilities